PENGUKURAN KADAR PIRIDOKSIN (VITAMIN B6) DALAM DARAH PADA ANAK PENDERITA DEFISIT PERHATIAN DAN GANGGUAN HIPERAKTIVITAS (ADHD) - Melvariani Syari Batubara; Yahwardiah Siregar; Herla Rusmarilin; Sri Soviani (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2018)
This research aimed to study Piridoksin (Vitamin B6) status in blood sample of Attention Deficit Hyperactivity Disorder (ADHD) children. Deductive research using the descriptive method through 2 stage, namely : (1) Taken of blood sample, and (2) Analysis of Piridoksin (Vitamin B6) status in blood sample was performed by using High Performance Liquid Chromatograpy (HPLC) method. Data collected and assessed by once in one time. Data were analyzed using descriptive analysis techniques and Chi Square tests (X2) by Computer programs (SPSS 15). The result of the assessment of Piridoksin (Vitamin B6) status in blood sample of ADHD children that had been was considered statistically highly significant a reduce of the assessment of Piridoksin (Vitamin B6) status in blood sample of ADHD children by 0,422 ng/ml compared with laboratory reference (control) by 0,36-1,8 ng/ml, HA<C** (p<0,001). This was considered a reduction in Piridoksin (Vitamin B6)) concentrations induces of the Hyperactivity children by 95%.